(untitled) (Journal of the Bangladesh Agricultural University, 2020)
The study attempted to find out the relationship and estimates the growth rates of area, production, and yield of pulse, oilseeds and sugarcane in Bangladesh using secondary data covering the period from 1997-98 to 2017-18 through exponential model, correlation coefficient and simple linear regression model. Here, the whole period was divided into two sub periods such as period-I (1997-98 to 2007/08) and period-II (2008-09 to 2017-18). Results indicated that high correlation exist between area and production of pulse, and sugarcane and low correlation between area and production of oilseed. During the whole period (1997/98-2017/18), overall production on area of pulse and sugarcane have been increased except oilseeds (r=0.112). Growth rates of area which was negative but significant for pulse, oilseeds and sugarcane were 2.9, 0.04 and 3.6%, respectively. The growth rates of area of pulse, sugarcane and oilseeds were negative in period-І. But in period-ІІ, area of pulse and oilseeds grew significantly at the rate of 6.3% and 3.1%, respectively. Growth rates of production which was significantly negative for pulse (1%) and sugarcane (3.4%) respectively and positive for oilseeds (5.4%) during the whole period. In period-І, production growth rates of pulse and sugarcane were negative but in period-II, production of pulse and sugarcane grew significantly at the rate of 8.7% and 3.8%, respectively. Growth rates of yield were significantly positive for pulse, oilseeds and sugarcane during the overall period. In period-І and period-II, pulse and oilseeds yield growth rates were found positive but yield of sugarcane grew positively in period-II than previous period. Analyzing the growth rates of area, production and yield of pulse, sugarcane and oilseed may guide the farmers allowing rational distribution of area which would enhance the production of these crops in Bangladesh. J Bangladesh Agril Univ 18(3): 700–707, 2020 https://doi.org/10.5455/JBAU.103725